Bloodlands [compact disc, unabridged] : Europe between Hitler and Stalin - Snyder, Timothy (Blackstone Audio, 2010)
Timothy Snyder examines the bloody legacy left by World War II tyrants Adolph Hitler and Joseph Stalin.